Implementasi Metode Extreme Programming Untuk Merancang Sistem Informasi Payroll Pada PT. Jala Artha Karya - Lilyani Asri Utami; Alby Sukmana (Informatics and Computer Engineering Journal, 2024)
Information systems provide additional benefits for the organization and business of PT. Jala Artha Karya, a general contractor company engaged in architecture, civil construction, mechanical and electrical, steel fabrication, tower construction and consultant. At PT. Jala Artha Karya, the payroll or salary and attendance system is currently still done manually through recording on a worksheet, which sometimes results in data redundancy and difficulty in making reports because they must be summarized first, and has the potential for abuse of authority and data manipulation. Therefore, it is necessary to design an information system for payroll at PT. Jala Artha Karya. The development of this information system is website-based and uses the Extremel Programming (XP) method, which is a simple software development approach and includes one of the agile methods developed by Kent Beck, Ron Jeffries, and Ward Cunningham. XP is one of the most popular agile methods and has become a very well-known approach in the world of software development. With the implementation of a website-based payroll information system at PT. Jala Artha Karya is expected to help manage payroll and attendance more effectively and efficiently.